Фільтрація струмів в трифазній трипроводній системі електроживлення при несиметричних синусоїдних напругах - Артеменко, М.Ю.; Батрак, Л.М.; Поліщук, С.Й. (Електротехніка і електромеханіка, 2018)
Розглянуто принципи активної фільтрації струму в трифазній трипровідній системі електроживлення при несиметричному синусоїдному джерелі живлення, що задовольняють вимогам стандарту IEEE Std.1459-2010. Показано переваги формування синусоїдного симетричного вхідного струму при паралельному підключенні активного фільтра та реактивного компенсатора. Доведено можливість компенсації неактивного синусоїдного струму Фрізе реактивними елементами при довільній комбінації параметрів лінійного навантаження та джерела. Отримана формула прямого розрахунку параметрів реактивного компенсатора для генерації неактивного струму Фрізе в несиметричному режимі трифазного джерела. Наводяться результати чисельного моделювання. Рассмотрены принципы активной фильтрации тока в трехфазной трехпроводной системе электропитания при несимметричном синусоидальном источнике питания, удовлетворяющие требованиям стандарта IEEE Std.1459- 2010. Показаны преимущества формирования синусоидального симметричного входного тока при параллельном подключении активного фильтра и реактивного компенсатора. Доказана возможность компенсации неактивного синусоидного тока Фризе реактивными элементами при произвольной комбинации параметров нагрузки и источника. Получена формула прямого расчета параметров реактивного компенсатора для генерации неактивного тока Фризе в несимметричном режиме источника питания. Приводятся результаты численного моделирования. Purpose. Investigation of the optimal current distribution between source, shunt active filter and reactive compensator of a three-phase three-wire system that provides consumption of a sinusoidal symmetric current under asymmetric source voltages with minimal power losses was provided. Methodology. The tasks were solved by conducting theoretical and experimental studies. The main provisions of the theory of electrical circuits, the apparatus of mathematical analysis, methods for solving linear differential and algebraic equations, elements of matrix and complex calculus and vector algebra are used. During the development, modern methods and software of computer simulation of electrical engineering complexes and dynamic systems were applied: Matlab-Simulink, MATHCAD. Originality. The principle of compensating current distribution between PAF and reactive compensator of a three-phase three-wire power system with asymmetric sinusoidal voltage was proposed at which the input current is equal to the positive-sequence active current and rms value of PAF current is minimal. The feasibility to compensate the inactive sinusoidal Fryze current by reactive elements under arbitrary combination of load and source parameters was proved and expression for direct calculation of the reactive compensator parameters for generation of inactive Fryze current in the source unbalanced mode was obtained. Practical value. The simulative example for transmission line load showed that combined application of PAF and reactive compensator with the specified distribution of compensating currents ensured a reduction of power losses in 3.273 times and rms value of the SAF current is 12.9 % of rms value total compensation current